The Cornerstone of Sustainability: Ecological Footprint - Ece Tuğba Mızık; Zehra Yiğit Avdan (Doğal Afetler ve Çevre Dergisi)
With the increase of human population and the development of technology, the demand for Natural Resources is increasing day by day. The natural resources used to supply the needs of production and consumption are destroyed and used thoughtlessly because of people's belief that they own the world. The term of ecological footprint is a numerical method used for sustainable usage of resources. Ecological footprint expression is a numerical method for sustainable use of resources. This method represents whole of the concepts of ecological economy and sustainability which that present ecological resources have economic value. This method represents a whole of the concepts of Ecological Economics and sustainability, which indicate that ecological resources have economic values. The concept of ecological footprint digitizes ecological resource consumption by ensuring that the amounts of ecologically efficient resources consumed and those resources are determined on a field basis. Recently, as a result of the interdisciplinary evaluation of the concept of sustainability, the concept of ecological footprint has been expanded and the concept of footprint family has been created. The footprint family provides the sustainability of each resource by ensuring that the consumption of ecological resources is assessed on a resource-by-resource basis. In this study, a detailed review of the history of the ecological footprint concept, which plays a key role in the sustainable management of ecological resources, and the footprint family that is effective in the management of resources, has been conducted.